Environmental Effects of Electrically-Stressed Sulfur Hexafluoride - Palaiologopoulou Maria D.; Mergos John A.; Dervos Constantine T. (EPJ Web of Conferences, 2012)
High Voltage (HV) equipment such as power switches, current or voltage transformers, and flexible HV transmission lines insulated by pressurized SF6 (or SF6/N2 mixtures) offer component compactness, high reliability and low maintenance demands compared to all conventionally insulating components (i.e. air, organic solid insulants, and mineral oils). Though SF6 insulation for HV applications was initially proposed during late ‘60s, it was spread worldwide rapidly due to offered significant economic advantages, and now SF6 GIS substations dominate the share in electrical networks in densely populated districts. However, it was in mid ‘90s when the first ecological concerns were brought about the SF6 gas use. These mainly stream out by either of the following facts: (i) SF6 is a strong green-house gas with a global warming potential of almost 25,000 greater than that of CO2 and its molecules exhibit an exceptionally high lifetime in earth atmosphere estimated to vary between 750 and 2500 years, and (ii) when electrically stressed (independent of temperature i.e. either high-power arcs developing at 20,000K during the switching actions, or corona discharges developing at 300K due to high electric field effects) toxic byproducts may be formed, some having high cyto-toxicities i.e. S2F10, oxyfluorides, H2S and HF.